2021
DOI: 10.1038/s41598-021-00296-5
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of silver nanoparticles using Plantago lanceolata extract and assessing their antibacterial and antioxidant activities

Abstract: Silver nanoparticles (Ag. NPs) have shown a biological activity range, synthesized under different environment-friendly approaches. Ag. NPs were synthesized using aqueous crude extract (ACE) isolated from Plantago lanceolata. The ACE and Ag. NPs were characterized and assessed their biological and antioxidant activities. The existence of nanoparticles (NPs) was confirmed by color shift, atomic force microscopy (AFM), and UV–Vis’s spectroscopy. The FT-IR analysis indicated the association of biomolecules (pheno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
22
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(34 citation statements)
references
References 71 publications
5
22
1
Order By: Relevance
“…The mentioned concentrations for total killing are very low compared to other reported green AgNPs. For instance, recently, Shah et al (2021) showed that the LD50 dose (concentration of AgNPs causing 50% inhibition) obtained from Plantago lanceolate against E. coli was 45.54 mg/L, which is much higher than the G-AgNPs MBC value (kill 100% bacteria) against E. coli, i.e., 8 µg/mL, in our study. Similarly, Devanesan and AlSalhi, 2021 demonstrated the antimicrobial activity of AgNPs originated from flower extract of Abelmoschus esculentus.…”
Section: Discussioncontrasting
confidence: 52%
“…The mentioned concentrations for total killing are very low compared to other reported green AgNPs. For instance, recently, Shah et al (2021) showed that the LD50 dose (concentration of AgNPs causing 50% inhibition) obtained from Plantago lanceolate against E. coli was 45.54 mg/L, which is much higher than the G-AgNPs MBC value (kill 100% bacteria) against E. coli, i.e., 8 µg/mL, in our study. Similarly, Devanesan and AlSalhi, 2021 demonstrated the antimicrobial activity of AgNPs originated from flower extract of Abelmoschus esculentus.…”
Section: Discussioncontrasting
confidence: 52%
“…These phytocompounds may play a role in stabilizing the particle size of the prepared silver metals within the nanoparticle ranges. Similar FT-IR results were reported in previous studies of green synthesized AgNPs 16 , 31 , 32 . The chemical AgNPs FT-IR spectrum peaks were corresponding to the O–H stretching/N–H stretching of an amine group and C=O groups.…”
Section: Discussionsupporting
confidence: 90%
“…According to the ICDD PDF-2 (No.071-4613) database, these lattice planes were indexed to the face-centered cubic crystal (FCC) nature of metallic silver. The average crystallite size of the AgNPs was calculated by applying the Scherrer equation 16 . Cinnamon, ginger, and chemical AgNPs' average crystallite sizes were 5.7, 10.3, and 14.6 nm, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations